La disposición de secciones de propiedad exclusiva bajo el dominio de la Junta de Propietarios en el régimen de propiedad exclusiva y propiedad común - Losno Perleche, Jhon (2022)
The present research work deals with the alienation of sections of exclusive property, whose ownership corresponds to the Board of Owners, within the framework of the horizontal property regime. Firstly, the legal nature of the Board of Owners is addressed in order to explain its relative legal subjectivity, which allows it to act in a unitary manner in the legal sphere, but with joint and several liability of its members. Secondly, I disagree with the position taken by the Registry Court which states that a qualified majority is required to have exclusive sections: I argue that only an absolute majority is required. Thirdly, I point out that, in order for the disposal of an exclusive section to proceed with the absolute majority that I propose, the purpose of the property must be the subsequent sale, and the third party acquirer will have good faith only if such purpose of the property existed in the deeds filed at the time of the sale; if the purpose was not that, then a qualified majority must be required (this constitutes an exception to the rule that I propose of absolute majority). Then, I indicate that the formalization of the transfer agreement of exclusive sections is materialized by Public Deed and publicized through the registry registration, in order to comply with the principle of authentic title and registry public faith respectively. Finally, I recommend amending articles 43 of Law 27157 and 135 of its Regulations to indicate that the Board of Owners may dispose of sections of exclusive property; as well as amending articles 47 of the same Law and 145 of its Regulations.